Analisis Faktor-faktor yang Mempengaruhi Produktivitas Tenaga Kerja pada Proyek Rehabilitasi dan Renovasi Gedung BPJS Kesehatan Kantor Cabang Ambon: Analysis of Factors Affecting Labor Productivity in the Rehabilitation and Renovation Project of the BPJS Kesehatan Ambon Branch Office Building - Tutupoho, Badrun; Serang, Rudi; Langi, Jeffrey Payung (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Rehabilitation and Renovation Project of BPJS Kesehatan Ambon Branch Office Building, on Jl. Ir. M. Putuhena, Wailela, Rumah Tiga Kec. Teluk. Ambon, Ambon City-Maluku is one of the projects funded by APBN funds with a contract value of Rp. 14,750,000,000.00. This study aims to obtain the influence of factors on labor productivity and obtain the most dominant factors on labor productivity in the Rehabilitation and Renovation Project of BPJS Kesehatan Ambon Branch Office Building. The data collection method used by the author in this study is the Observation Method, the author conducted a field survey on the Project which was the object of the study, to obtain primary data in the form of interviews with the implementing contractor at the project location and secondary data in the form of General Project Drawings and Labor Data obtained from the implementing contractor. in the implementation of the Rehabilitation and Renovation Project of BPJS Kesehatan Ambon Branch Office Building. Based on the results of the analysis of the presentation of the influence of independent variables on labor productivity, which is 75.2%. While the remaining 24.8% is influenced by other variables that were not tested in this study, and the most dominant influencing factor on labor productivity in the BPJS Kesehatan Ambon Branch Office Building Rehabilitation and Renovation Project was obtained, which was seen from the results of the highest standardized coefficients beta value, namely in the Education Variable (X3) of (0.834) or (83.4%). So the most dominant factor is the Education Variable.